New Genetics, New Social Formations - Glasner, Peter; Atkinson, Paul (Genetics and Society, 2007)
New genetic technologies cut across a range of public regulatory domains and private lifeworlds, often appearing to generate an institutional void in response to the complex challenges they pose. As a result, a number of new social formations are being developed to legitimate public engagement and avoid the perceived democratic deficit that may result. Papers in this volume discuss a variety of these manifestations in a global context, including: genetic data banks committees of inquiry non-governmental organisations (NGOs) national research laboratories. These institutions, across both health and agriculture, are explored in such diverse locations as Amazonia, China, Finland, Israel, the UK and the USA. This volume exhibits a clear thematic coherence around the impact of the new genetics and their associated technologies on new social formations, and the case studies included have a significant international focus, showing a balance between theoretical and empirical approaches in this rapidly changing field. This innovative new volume will be of interest to postgraduates and professionals in the fields of sociology, social anthropology, science and technology studies, and environmental studies.